Kajian Struktur Keperibadian Dalam Psikoanalisis : Watak-Watak Terpilih Dalam Skrip Atap Genting Atap Rumbia Karya Kala Dewata. - Mohd Abdul Rahman, Zurin (Universiti Malaysia Sarawak (UNIMAS), 2020)
The Study of Personality Structures in Psychoanalysis: Selected Characters in the Atap Genting Atap Rumbia by Kala Dewata is a descriptive qualitative work and uses a content analysis approach to analyse texts and other reading material. Atap Genting Atap Rumbia script are studied using the theory of personality structure in psychoanalysis. The application of certain concepts through the theory of psychoanalysis pioneered by Sigmund Freud was used in this study. In the meantime, this study also explores the personal structure of Id, Ego and Superego for the characters in the Atap Genting Atap Rumbia script. The textual study method is qualitatively taken in terms of the life cycle and social aspects the character in the script to be included in the study to achieve the objective of the study. Through this study, topographical maps of human personality, Id, Ego and Superego can be applied to this manuscript.